Measurement of the Maturity Level of Micro, Small, and Medium Enterprises (MSMEs) Business Processes in East Kotawaringin Regency during the Covid-19 Pandemic - Bachtiar, Lukman; Riyadi, Slamet (Politeknik Dharma Patria Kebumen, 2021)
MSMEs (Micro, Small, and Medium Enterprises) have an important role in creating new jobs. Currently, MSMEs as one of the economic foundations are expected to be able to compete in the era of free trade, both in local and international. One of the strengths that are expected to be able to compete is by improving business processes and increasing information technology capabilities. The use of Information Technology (IT) changes the way in business processes in MSMEs. The current condition is that MSMEs are not ready to implement IT and its infrastructure. This study aimed to determine the quality of business process maturity and IT availability in small MSMEs. The method used in this research was the Business Process Orientation Maturity Model (BPOMM). The results of the analysis show that the maturity level is in the defined category with a final value of 5.36. The assessment of IT availability is 2.75 with the highest score is found in IT HR.